Dampak Metode Latihan Sirkuit dan Interval terhadap Peningkatan Kecepatan Tendangan Dollyo Chagi Atlet Taekwondo Dojang Bhirawa Jatitengah - Raka Chandra Imanda; Slamet Santoso; Sunjoyo (MAN Insan Cendekia Jambi, 2026)
This study aims to: (1) identify the differences in the influence of the Circuit Training and Interval Training methods on the speed of Taekwondo dollyo chagi kicks, (2) understand the more effective technique between Circuit Training and Interval Training. The research design used was a two-group experiment, with each group given a pretest before treatment and a posttest after treatment. The group division used ordinal pairing in this study. The population at Dojang Bhirawa Jatitengah was 25 people, and a sample of 20 people was used. Implementation instructions: (1) collect test data, (2) provide infrastructure, (3) do as many dollyo chagi kicks as possible towards the target within 1 minute. The analysis results show a significant difference in the influence between the circuit training method and interval training on the speed of the dollyo chagi kick of Taekwondo athletes. Based on the results of the t-test, the calculated t-value of 3.732 was obtained, which is higher than the t-table value of 2.262 at a significance level of 5%. This finding indicates that both training methods play an equal role in increasing the speed of the dollyo chagi kick. However, the group undergoing circuit training showed an increase of 9.06%, while the interval training group experienced an increase of 7.65%. Therefore, it can be concluded that the circuit training method has a more dominant influence than the interval training method.